One Layer Extramucosal-Seromusculer Bowel Anastomosis In Children - Kazez, Ahmet; Sağlam, Metin; Apak, Sami; Parmaksız, Ergun; Demirbağ, Mustafa (Fırat University, 2001)
In this study we present our experience about using a single layer extramucosal-seromusculer (EM-SM) suture technique to construct intestinal anastomosis in children. Between September 1996 and April 1999, we created 51 intestinal anastomosis in 45 patients using a single-layer, EM-SM technique with synthetic absorbable suture (polyglactin or polydioxanone). Conventional bowel preparation was utilised in all enterostomised cases. There were no complications related to the anastomosis. One patient, who was operated for ileal atresia had superficial wound infection. These results are thought that the (EM-SM) technique is easier and reliable as well as the other techniques.

Bu çalışmada, çocuklarda ekstramukozal-seromüsküler (EM-SM) tek kat dikiş tekniği kullanılarak gerçekleştirilen barsak anastomozu ile ilgili deneyimlerimizi sunuyoruz. Eylül 1996 - Nisan 1999 tarihleri arasında, Polyglactin veya Polydioxanone sütürleri kullanılarak, tek kat EM-SM tekniği ile, 45 hastada 51 intestinal anastomoz gerçekleştirildi. Enterostomili olguların hepsinde konvansiyonel barsak temizliği uygulandı. Olguların hiçbirinde anastomoz ile ilgili herhangi bir komplikasyon gelişmedi. İleal atrezi nedeni ile ameliyat edilen bir olguda yüzeyel yara enfeksiyonu gelişti. Bu sonuçlar EM-SM anastomoz tekniğinin kolay ve diğer anastomoz teknikleri kadar güvenilir olduğunu düşündürmektedir.
ÇOCUKLARDA EKSTRAMUKOZAL - SEROMÜSKÜLER TEK KAT BARSAK ANASTOMOZU